Measurement Properties of the Chinese Weinstein Noise Sensitivity Scale - Fong, Daniel Y.T. (Noise Health, 2017)
CONTEXT: Noise sensitivity may mediate or moderate the influences of noise exposure on health, and it needs to be reliably evaluated. The 21-item Weinstein’s noise sensitivity scale (WNSS) has been the most popular scale for assessing noise sensitivity, but it is not yet available in traditional Chinese. AIMS: This study aimed to conduct linguistic and psychometric performance of WNSS in Hong Kong (HK) Chinese. SETTINGS AND DESIGN: A population-based telephone survey with 1-week follow-up. MATERIALS AND METHODS: The HK Chinese WNSS was obtained after forward–backward translation from the original English version and cognitive debriefing in five Chinese adults. Its measurement properties were assessed in 569 Chinese adults aged 18 years or above. STATISTICAL ANALYSIS USED: The sample was randomly split into two halves. The first half was used to explore a scale structure of the WNSS by exploratory factor analysis (EFA) with the number of factors determined by the optimal comparison data technique and tested for being artifactual. The second half was used for confirmatory factor analysis. Convergent validity and test–retest validity were also assessed. RESULTS: EFA identified two unipolar factors and removed three items poorly associated with the factors. The factors were likely artifactual and a unidimensional structure was assessed in CFA, which showed a satisfactory fit (root mean square error of approximation = 0.055; comparative fit index = 0.904; standardized root mean square residual = 0.061). The HK Chinese WNSS had good internal consistency (Cronbach’s α = 0.83) and test–retest reliability (intraclass correlation coefficient = 0.87). Furthermore, it confirmed the expected association with extraversion (r = −0.14, P < 0.001) and neuroticism (r = 0.28, P < 0.001). CONCLUSION: The 18-item HK Chinese WNSS was reliable and valid for assessing noise sensitivity in the Chinese population.